Uncropped [videorecording (DVD)] - Ullmann, David (Greenwich Entertainment ; Kino Lorber, 2024)
In Uncropped, legendary Village Voice photojournalist James Hamilton recounts the stories behind iconic images taken over the course of a forty-year career. This is a visual chronicle of New York City and a window into the heyday of alternative print media. Alfred Hitchcock. Muhammed Ali. Meryl Streep. LL Cool J.--James Hamilton captured them all.